SISTEM KENDALI PID PADA PENGATURAN KECEPATAN MOTOR INDUKSI TIGA FASA BERBASIS PLC SCADA - Dorkas, Rahel; -, Yurika (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
The rapid advancement of technology has driven industries to enhance production efficiency, one of which is through the use of three-phase induction motors as the primary drivers of industrial machinery. Despite their advantages in terms of simple construction, reliability, and energy efficiency, three-phase induction motors still face challenges in speed regulation. To address this issue, this study developed a speed control system for three-phase induction motors using a Variable Frequency Drive (VFD), Programmable Logic Controller (PLC), and Supervisory Control and Data Acquisition (SCADA). The system is equipped with Proportional Integral Derivative (PID) control to maintain a constant motor speed, even under varying load conditions. Testing results demonstrated that the system effectively maintained motor speed near the setpoint with a fast, stable response and minimal overshoot. Additionally, SCADA was utilized to monitor and control motor parameters in real-time. However, there is a decrease in performance at low frequencies due to sensor limitations. This research highlights the effectiveness of PID control in regulating three-phase induction motor speed and makes a significant contribution to the development of motor control systems in the industrial sector.